2N+4-rule and an atlas of bulk optical resonances of zigzag graphene nanoribbons - Renebeth B. Payod (Nature Portfolio, 2020)
The authors combine ab-initio density functional theory with tight-binding calculations to investigate the optical absorption resonances of armchair carbon nanotubes and zigzag graphene nanoribbons, and show that an atlas of carbon nanotubes optical transitions can be mapped to an atlas of optical resonances of zigzag graphene nanoribbons.